Biocomputation and biomedical informatics : case studies and applications - Lazakidou, Athina A. , 1975- (Medical Information Science Reference, 2010)
"This book provides a compendium of terms, definitions, and explanations of concepts, processes, and acronyms"--Provided by publisher.